Genes and Morality New Essays - Launis, Veikko; Pietarinen, Juhani; Raikka, Juha (Value Inquiry Book Series, 1999)
Most public discussion has focused on those effects of genetic research that are considered in some way unwanted or unpleasant. For example, there has been much debate concerning the risks and the ethical appropriateness of genetic screening, gene therapy, and agricultural applications based on genetic techniques. It often claimed that genetic research may cause new problems such as genetic discrimination, stigmatization, environmental risks, or mistreatment of animals. Genes and Morality: New Essays adopts a critical attitude toward genetic research, on both a theoretical and a practical level. It presents some of the most important problems in the ethics of genetic engineering, including the questions of genetic health and disease, genetic testing, responsibility for health, patenting non-human and human life, and problems related to the disclosure of genetic information. The aim of the book is to focus on real ethical and conceptual issues. Consider, for instance, the concept of genetic disease. As one of the contributors, Ingmar Pörn, writes, fear of genetic disease, or anxiety, is not itself a disease any more than fear of becoming unemployed is a disease. Alleviating such emotions is not a medical task to be discharged by drug therapy. The book also examines the philosophical foundations of these issues by discussing the most influential bioethical theories of today, including utilitarianism and principlism.